XVI Seminario sobre amibiasis 2009 y embo workshop: amebiasis, molecular approaches in an important but neglected disease - Lim Boon, Huat (Pusat Pengajian Sains Perubatan, 2009)
Amoebic liver abscess (ALA) is the most common extraintestinal manifestation of amoebiasis in South East Asian countries and Mexico. Diagnosis is based on clinical symptoms and signs; occurrence of space occupying lesion in liver detected by imaging techniques, positive amoebic serology and clinical response to antiamoebic therapy with metronidazole. The amoebic serological assay employed at Hospital Universiti Sains Malaysia (HUSM), Kelantan is the commercial indirect haemagglutination assay (IHA) kit which detects anti-Entamoeba histolytica antibodies in serum samples. During the study period from January 2005 till June 2006, there were 43 clinical or suspected cases of ALA. On admission, all patients presented with fever. Thirty nine of them had abdominal pain; 9 had history of passing loose stools; 42 presented with hepatomegaly while 15 had jaundice; and 37 presented with leucocytosis. Thirty three patients had liver abscesses in their right lobe, 6 with abscesses in the left lobe and 4 had abscesses in both lobes of the liver. The IHA test were positive (titer more than or equal to 1 :256) in 33 (76.7%) patients. Forty two of the patients were treated with intravenous metronidazole 500 mg every 8 hours and continued with oral metronidazole when the patients were discharged. In the amoebiasis endemic setting in Kelantan, interpretation of IHA results can be problematic due to the high background antibody levels Therefore, a simple, rapid, noninvasive test with high sensitivity and specificity for laboratory diagnosis of ALA is urgently needed.